The Relationship Between Economic Integration, Economic Growth and High Technology: Eurasian Economic Integration and Turkey - Çakmaklı Bahadır Murat (Studia Ekonomiczne i Regionalne)
Economic integration is an extremely important institutional structure for countries in international trade, which is highly competitive, with the level of globalisation, innovation and communication technology.